The Effect of Organizational Strategy and Infrastructure Management on the Performance of Junior High School Teachers in Wenang Manado District - Heldy Rogahang (Peneliti.net, 2020)
Purpose of this study was to examine the influence of organizational strategy and infrastructure management on the performance of vocational high school teachers. The research used quantitative methods and the research design used path analysis. The population of this study were 35 junior high school teachers in the district. Manado authority. The results showed that: 1) there is a positive direct effect on organizational strategy in improving performance, 2) there is a positive direct effect of infrastructure management advice on performance.